NKG2A Down-Regulation by Dasatinib Enhances Natural Killer Cytotoxicity and Accelerates Effective Treatment Responses in Patients With Chronic Myeloid Leukemia - Chang, Ming-Chin; Cheng, Hung-I; Hsu, Kate; Hsu, Yen-Ning; Kao, Chen-Wei; Chang, Yi-Fang; Lim, Ken-Hong; Chen, Caleb Gonshen (Frontiers in Immunology, 2019)
Chronic myeloid leukemia (CML) is a hematological malignancy characterized by the presence of t(9;22) chromosomal translocation that results in BCR-ABL fusion gene. ABL tyrosine kinase inhibitors (TKIs), such as imatinib, nilotinib, and dasatinib, are currently the front-line treatment options for CML. Recently, natural killer (NK) cell activation and expansion have been shown to be associated with optimal treatment responses for CML. To investigate the effects and mechanisms of these TKIs on NK cells, here we characterized activating and inhibitory NK receptors in CD3−CD16+CD56dim NK cells isolated from CML patients in chronic phase (CP). The expressions of activating NK receptors, such as NKG2D, natural cytotoxicity receptor (NCR) and DNAM-1, rebounded after successful TKI treatments for CML. In contrast, among the three surveyed inhibitory receptors (NKG2A, KIR2DL1, and KIR3DL1), only the expression of NKG2A was reverted and suppressed to a very low level by dasatinib, and not by imatinib or nilotinib. CML patients treated with dasatinib indeed expressed fewer NKG2A+ NK cells, which send negative signals for induction of NK cytotoxicity. For these dasatinib-treated patients, the duration to reach major molecular response (MMR) was shorter, and significantly correlated with individual's NKG2A+ NK cell number. This clinical relevance to NKG2A was not observed in treatments with imatinib or nilotinib. In line with dasatinib-specific down-regulation of NKG2A, NK cytotoxicity evaluated by the killing assay was also significantly higher in patients treated with dasatinib than in those treated with imatinib or nilotinib. The lower NK cytotoxicity from imatinib or nilotinib treatments could be reverted by NKG2A blockade using anti-NKG2A antibody. Further in vitro experiments revealed mechanistically that dasatinib could inactivate p38 mitogen-activated protein kinase (MAPK), and consequently affect nuclear import of GATA-3 and GATA-3 transcriptional activities for NKG2A. Our results highlight the dual effects of dasatinib in direct inhibition of ABL kinase and in immunomodulation through NKG2A down-regulation, contributing to accelerated molecular responses (MR) in CML.